2022
DOI: 10.1002/smll.202107417
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Interface‐Exciting Catalysis on Cobalt Nitride‐Oxide for Accelerating Hydrogen Generation

Abstract: The rational design of the interface structure between nitride and oxide using the same metallic element and correlating the interfacial active center with a determined catalytic mechanism remain challenging. Herein, a Co4N‐Co3O4 interface structure is designed to determine the effect of interfacial active centers on hydrogen generation from ammonia borane. An unparalleled catalytic activity toward H2 production with a turnover frequency up to 79 min−1 is achieved on Co4N‐Co3O4@C catalyst for ten recycles. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…In addition, the catalytic activity of Ru 0.8 Ni 0.2 /MoS 2 with that of other reported catalysts in dimethylamineborane hydrolysis was further summarized and is compared in Table . The result showed that as-obtained Ru 0.8 Ni 0.2 /MoS 2 exhibited the excellent catalytic performance in H 2 release upon dimethylamineborane hydrolysis, with 7199 mol (H 2 )·mol cat –1 ·h –1 at 30 °C under 2 M NaOH, which exceeds almost other reported catalysts. …”
Section: Resultsmentioning
confidence: 95%
“…In addition, the catalytic activity of Ru 0.8 Ni 0.2 /MoS 2 with that of other reported catalysts in dimethylamineborane hydrolysis was further summarized and is compared in Table . The result showed that as-obtained Ru 0.8 Ni 0.2 /MoS 2 exhibited the excellent catalytic performance in H 2 release upon dimethylamineborane hydrolysis, with 7199 mol (H 2 )·mol cat –1 ·h –1 at 30 °C under 2 M NaOH, which exceeds almost other reported catalysts. …”
Section: Resultsmentioning
confidence: 95%
“…Reproduced with permission. [ 149 ] Copyright 2022, Wiley‐VCH. d,e) Comprehensive morphology characterization of g‐C 3 N 4 .…”
Section: In‐depth Discussion On Supported Catalystsmentioning
confidence: 99%
“…Subsequently, Li designed Co (N) * and Co (O) * double active sites and combined the double active sites with AB and H 2 O molecules to analyze the reaction path (Figure 31e). [ 149 ] The specific reaction path is as follows: NH3BH3badbreak+Cofalse(normalNfalse)goodbreak=NH3BH2goodbreak−Cofalse(normalNfalse)goodbreak+H$$\begin{equation}{\rm{NH}}_3{\rm{BH}}_3 + {\rm{Co}}_{({\rm{N}})}^* = {\rm{NH}}_3{\rm{BH}}_2 - {\rm{Co}}_{({\rm{N}})}^* + {{\rm{H}}}^*\end{equation}$$ H2normalObadbreak+Cofalse(normalOfalse)goodbreak=HOgoodbreak−Cofalse(normalOfalse)goodbreak+H$$\begin{equation}{{\rm{H}}}_2{\rm{O}} + {\rm{Co}}_{({\rm{O}})}^* = {\rm{HO}} - {\rm{Co}}_{({\rm{O}})}^* + {{\rm{H}}}^*\end{equation}$$ NH3BH2Co(N)+normalH+HOCo(O)+normalH=HOCo(O)+NH3BH2OHCo(N)+normalH2$$\begin{eqnarray} && {\rm{NH}}_3{\rm{BH}}_2 - {\rm{Co}}_{({\rm{N}})}^* + {\rm{ H}}^* + {\rm{HO}} - {\rm{Co}}_{({\rm{O}})}^* + {{\rm{H}}}^* \nonumber \\ && \quad = {\rm{HO}} - {\rm{Co}}_{({\rm{O}})}^* + {\rm{NH}}_3{\rm{BH}}_2{\rm{OH}} - {\rm{Co}}_{({\rm{N}})}^* + {{\rm{H}}}_2 \uparrow \end{eqnarray}$$ …”
Section: Investigation Of the Catalytic Mechanism And Pathway Of Abmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also found that catalytic activity of the Pt 0.7 Ni 0.3 /CNS nanohybrid had been greatly enhanced, from 4955 to 16,607 mol (H 2 )·mol cat –1 ·h –1 by aqueous alkali. This is probably because the electron density of Pt atoms was enriched by the coordination of OH – anion, which is in favor of the breaking of a water O – H bond. …”
Section: Discussionmentioning
confidence: 99%